NECESSARY OR COMPULSORY: STUDENTS' PERCEPTION ON SCIENTIFIC WRITING AND EVERYTHING IN BETWEEN - Siti Hadianti; Benny Nugraha; Ika Tri Yunianika (English Review: Journal of English Education, 2023)
The presence of scientific writing as a new compulsory course attracts educational institutions, including Universitas Terbuka. Not only because the course is a new course, which means many possible and valuable reactions to it, but also due to the puzzling condition surrounding it. Like two sides of a coin, scientific writing is hoped to bring essential value. Therefore, students will perceive it positively, yet it also generates anxiety because the difficulty of the lesson itself needs to be digested through an online platform. This research is constructed to explore the issue. To make it easier to follow, we limit our concern to two research questions and one hypothesis. The first question is on how students perceive scientific writing courses and the second do students consider the course as necessary or compulsory. On the other side, we promote a hypothesis that argues that students will perceive the scientific course as necessary yet fail to internalize the skill from the course. This study uses a mixed method which can be utilized to answer the research question as well as the hypothesis. The sample is 47 participants that enroll in a scientific writing class using a nested sampling design. Based on quantitative analysis, it is found that the hypothesis is accepted and there are 3 levels of perception that can also answer the research question such as high, moderate, and low perception.